Implementation and Follow-up Experience of an e-Consult Program in a Rural Neurology Setting - Malik, Muhammad Taimur; Zand, Ramin; Vezendy, Shelly M; Newman, Eric; Holland, Neil R (Neurology. Clinical practice, 2021)
The demand for neurology services at Geisinger exceeds the current clinical capacity. Therefore, we implemented and assessed the utility of Ask-a-Doc (AAD), which is an electronic medical record-based interface developed at Geisinger to facilitate communication between primary care physicians (PCPs) and specialists. AAD was used at the end of 2015 in our department. Based on the clinical picture, the PCP assesses whether to send an urgent AAD question with a phone request or a more elective question that can be answered by email message. The AAD message is then relayed to the on-call neurologist. We analyzed 4-year longitudinal data to assess for the efficacy of this tool in our department in improving patient care and communication. There were a total of 3,190 messages during this period. Of which, 2,927 (91.7%) were completed and routed correctly, and 263 (8.3%) messages had errors including routing issues, communication mismatch, and delayed time frame. The average specialist turnaround time was 5 hours. During this period, the number of AAD messages increased by 300% as PCPs and neurologists became more comfortable with the process. AAD provides an interface between PCPs and neurology specialists and can assist in determining whether a patient needs to be seen urgently in the clinic, the correct subspecialty, and prerequisite diagnostic tests. AAD was successfully implemented and used in our rural neurology setting, with rapid turnaround, increased usage, and accuracy.